A Phase IIIb Study to Evaluate the Safety of Ranibizumab in Subjects with Neovascular Age-related Macular Degeneration - Boyer, David S.; Heier, Jeffrey S.; Brown, David M.; Francom, Steven F.; Ianchulev, Tsontcho; Rubio, Roman G. (Ophthalmology (Rochester, Minn.), 2009)
To evaluate the safety and efficacy of intravitreal ranibizumab in a large population of subjects with neovascular age-related macular degeneration (AMD). Twelve-month randomized (cohort 1) or open-label (cohort 2) multicenter clinical trial. A total of 4300 subjects with angiographically determined subfoveal choroidal neovascularization (CNV) secondary to AMD. Cohort 1 subjects were randomized 1:1 to receive 0.3 mg (n = 1169) or 0.5 mg (n = 1209) intravitreal ranibizumab for 3 monthly loading doses. Dose groups were stratified by AMD treatment history (treatment-naïve vs. previously treated). Cohort 1 subjects were retreated on the basis of optical coherence tomography (OCT) or visual acuity (VA) criteria. Cohort 2 subjects (n = 1922) received an initial intravitreal dose of 0.5 mg ranibizumab and were retreated at physician discretion. Safety was evaluated at all visits. Safety outcomes included the incidence of ocular and nonocular adverse events (AEs) and serious adverse events (SAEs). Efficacy outcomes included changes in best-corrected VA over time. Some 81.7% of cohort 1 subjects and 49.9% of cohort 2 subjects completed the 12-month study. The average total number of ranibizumab injections was 4.9 for cohort 1 and 3.6 for cohort 2. The incidence of vascular and nonvascular deaths during the 12-month study was 0.9% and 0.7% in the cohort 1 0.3 mg group, 0.8% and 1.5% in the cohort 1 0.5 mg group, and 0.7% and 0.9% in cohort 2, respectively. The incidence of death due to unknown cause was 0.1% in both cohort 1 dose groups and cohort 2. The number of vascular deaths and deaths due to unknown cause did not differ across cohorts or dose groups. Stroke rates were 0.7%, 1.2%, and 0.6% in the 0.3 mg and 0.5 mg groups and cohort 2, respectively. At month 12, cohort 1 treatment-naïve subjects had gained an average of 0.5 (0.3 mg) and 2.3 (0.5 mg) VA letters and previously treated subjects had gained 1.7 (0.3 mg) and 2.3 (0.5 mg) VA letters. Intravitreal ranibizumab was safe and well tolerated in a large population of subjects with neovascular AMD. Ranibizumab had a beneficial effect on VA. Future investigations will seek to establish optimal dosing regimens for persons with neovascular AMD. Proprietary or commercial disclosure may be found after the references.